2012
DOI: 10.1038/jid.2011.283
|View full text |Cite
|
Sign up to set email alerts
|

UVA1 Induces Cyclobutane Pyrimidine Dimers but Not 6-4 Photoproducts in Human Skin In Vivo

Abstract: UVB readily induces cyclobutane pyrimidine dimers, mainly thymine dimers (TTs), and pyrimidine (6-4) pyrimidone photoproducts (6-4PPs) in DNA. These lesions result in "UVB signature mutations" found in skin cancers. We have investigated the induction of TTs and 6-4PPs in human skin in vivo by broadband UVA1, and have compared this with comparable erythemal doses of monochromatic UVB (300 nm). In vitro and ex vivo studies have shown the production of TTs, without 6-4PPs, by UVA1. We show that UVA1 induces TTs, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
98
1
10

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(111 citation statements)
references
References 46 publications
2
98
1
10
Order By: Relevance
“…C are generated (but not 6-4PPs) in fibroblasts, keratinocytes, melanocytes, and human skin (Mouret et al 2006(Mouret et al , 2008(Mouret et al , 2011. Histoimmunochemical measurements confirmed the presence of CPDs in the epidermis, whereas 6-4PPs were not detected (Tewari et al 2012). Interestingly UVB-induced CPDs were predominantly located at the basal level of the epidermis in contrast to CPDs, whose concentration decreases as the depth increases (Tewari et al 2012).…”
Section: Uva-mediated Formation Of Cyclobutane Pyrimidine Dimersmentioning
confidence: 81%
See 1 more Smart Citation
“…C are generated (but not 6-4PPs) in fibroblasts, keratinocytes, melanocytes, and human skin (Mouret et al 2006(Mouret et al , 2008(Mouret et al , 2011. Histoimmunochemical measurements confirmed the presence of CPDs in the epidermis, whereas 6-4PPs were not detected (Tewari et al 2012). Interestingly UVB-induced CPDs were predominantly located at the basal level of the epidermis in contrast to CPDs, whose concentration decreases as the depth increases (Tewari et al 2012).…”
Section: Uva-mediated Formation Of Cyclobutane Pyrimidine Dimersmentioning
confidence: 81%
“…Histoimmunochemical measurements confirmed the presence of CPDs in the epidermis, whereas 6-4PPs were not detected (Tewari et al 2012). Interestingly UVB-induced CPDs were predominantly located at the basal level of the epidermis in contrast to CPDs, whose concentration decreases as the depth increases (Tewari et al 2012). The mechanism of formation of UVA-induced CPDs, which shows features of triple -triplet energy transfer with respect to the distribution of bipyrimidine photoproducts, has remained under debate until recently.…”
Section: Uva-mediated Formation Of Cyclobutane Pyrimidine Dimersmentioning
confidence: 91%
“…In fact, UVA radiation has been shown since the 1970s, first in bacteria (29) and then in mammalian cells (32,55,(80)(81)(82)(83)(84) and human skin (61,65,(85)(86)(87), to be also able to induce CPDs. However, these observations have been poorly considered until recently.…”
Section: Uva-induced Cpdsmentioning
confidence: 99%
“…[10] Given this fact, it seems at first not likely that UVA-1 might be capable of a significant IL-6 induction in vivo. However, recent work by Tewari et al [11] in vivo has demonstrated the capability of UVA-1 to also induce CPD in significant amounts. Thus, the DNA damage-related mechanism of IL-6 release was shown to exist also for the UVA-1 spectrum in vivo and this fits with our data.…”
Section: Discussionmentioning
confidence: 99%